A Systematic Literature Review : Pemetaan dan Pengelolaan Potensi Ekowisata dalam Peningkatan Kepariwisataan yang Mendukung Ekonomi Berkelanjutan - Awan Setia dharmawan; Mochamad Aan Sugiharto; Tutik Sulistyowati (STISIPOL Raja Haji, 2025)
Indonesia possesses natural beauty that rivals that of many other countries, making the current trend of utilizing natural potential as a foundation for tourism highly relevant. Ecotourism represents a fusion between industrial interests and environmental conservation, with the hope of promoting economic growth based on environmental sustainability. However, caution is necessary—when economic interests intersect with nature, there is a risk of fostering an anthropocentric mindset. Through the diverse natural and environmental resources found across Indonesia, it is hoped that more tourists will be attracted to visit, thereby contributing to the development of local economies. The tourism industry is one of the most dynamic and rapidly growing sectors today. It goes beyond mere travel, offering rich social and cultural experiences gained during the journey. The urgency of this research lies in its effort to develop a formulation for managing and harnessing ecotourism potential to enhance regional tourism. The goal of this study is to establish an effective management formulation and identify the potential of ecotourism in supporting regional tourism development. This research adopts a qualitative method, covering the process from problem formulation to data processing related to the management and potential of ecotourism. A literature review serves as the initial foundation for data collection in this study. The data analysis is conducted using the analytical tool VOSviewer, aimed at transforming data into visual representations or visual analyses. The research results show that there is an influence between the maintenance and management of ecotourism through various existing methods.